1985
DOI: 10.1126/science.2932797
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Factor: A Hormone Produced by the Heart

Abstract: Systematic studies on the significance of the secretory-like morphological characteristic of cardiac atrial muscle cells of mammals led to the finding that these cells produce a polypeptide hormone. This hormone, described in 1981 as atrial natriuretic factor (ANF), is diuretic (natriuretic), hypotensive, and has an inhibitory effect on renin and aldosterone secretion. Thus, ANF probably intervenes in the short- and long-term control of water and electrolyte balance and of blood pressure. Phylogenetically, ANF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
302
0
3

Year Published

1988
1988
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 950 publications
(309 citation statements)
references
References 54 publications
4
302
0
3
Order By: Relevance
“…3 Human atrial natriuretic peptide (hANP), a 28-aminoacid peptide hormone secreted predominantly by atrial cardiomyocytes, has diuretic, natriuretic, vasodilatory, aldosterone-inhibitory, and arterial BP-reducing effects. 4,5 Numerous physiological responses to exogenous ANP include a rapid natriuresis, diuresis and reduction in arterial BP in hypertensive laboratory animals and humans. 6 These findings suggest that ANP exerts a broad spectrum of beneficial effects for the treatment of hypertension, renal impairment and heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…3 Human atrial natriuretic peptide (hANP), a 28-aminoacid peptide hormone secreted predominantly by atrial cardiomyocytes, has diuretic, natriuretic, vasodilatory, aldosterone-inhibitory, and arterial BP-reducing effects. 4,5 Numerous physiological responses to exogenous ANP include a rapid natriuresis, diuresis and reduction in arterial BP in hypertensive laboratory animals and humans. 6 These findings suggest that ANP exerts a broad spectrum of beneficial effects for the treatment of hypertension, renal impairment and heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial natriuretic peptide is a novel hormone involved in the regulation of water and electrolyte homeostasis [1]. Quantitatively the most important source of ANP is the heart atria [2] but ANP has also been extracted from the heart ventricles [3,4], brain [2,5], eyes [6], adrenal gland [7], pituitary, lungs [8] and blood vessels [9].…”
Section: Introductionmentioning
confidence: 99%
“…6 Zimmerman et al reported that when α-ANP was infused exogenously at the lowest infusion rate in anesthetized dogs, the circulating α-ANP levels (increased to 31 ± 3 pg·mL -1 ) resulted in an increase of urine flow with no change in hemodynamic state. 7 Thus, it is possible that the increased plasma α-ANP levels exerted a diuretic action without any hemodynamic change in the present study.…”
Section: Résultats : Aucune Différence Intergroupe Significative N'a mentioning
confidence: 99%